Propuesta de un modelo de mejoramiento de la calidad del servicio al cliente del Miduvi de la provincia de Manabí - Almeida Quijije, María Leonela (2014)
The aim of this study was to evaluate the quality of service in order to determine the degree of user satisfaction in MIDUVI province of Manabí, and it was taken as a starting point the constant complaints by users. The research was descriptive, not experimental, for which it was developed and implemented a data collection instrument with a sample that involved 385 users who shared views and requirements to be improved. To do an amended multidimensional model SERVQUAL instrument is based on measuring the quality in five dimensions reliability, responsiveness, assurance, empathy and tangibles and this was adapted to a survey that allowed to measure the knowledge of customers services provided in this state. Among the findings, emphasizes that there is a high degree of satisfaction in any category, thus having the highest levels of satisfaction in the dimensions of empathy (72%), and safety (61 %) and within best strengths were the dimensions of tangibility is (56 %), reliability (55 %) and responsiveness (46%). It is concluded that the degree of satisfaction with the quality of service provided the entity by this study is positive.